The seller's liability for damages of the buyer as a form of legal protection buyers of mining excellent materials in Indonesia - Fransisca Maryane,; Made Warka,; Krisnadi Nasution, (Technium Social Sciences Journal, 2022)
This research is a normative legal research, namely legal research that focuses on positive legal studies. In the sale and purchase of mining minerals, buyers with good intentions get guaranteed legal protection through the seller's liability, which is based on the provisions of Article 1495, Article 582 and also Article 1977 of the Civil Code where buyers with good intentions can sue the seller who has cheating, including hidden defects that were not known at the time the agreement was agreed upon by the parties. Based on the provisions of these articles, the fraudulent seller must be responsible for all risks of loss suffered by the buyer, unless the buyer bears all these risks.